2022
DOI: 10.1111/jen.13023
|View full text |Cite
|
Sign up to set email alerts
|

Field margins and botanical insecticides enhance Lablab purpureus yield by reducing aphid pests and supporting natural enemies

Abstract: Botanical insecticides offer an environmentally benign insect pest management option for field crops with reduced impacts on natural enemies of pests and pollinators while botanically rich field margins can augment their abundance. Here, we evaluated the non-target effects on natural enemies and pest control efficacy on bean aphids in Lablab of three neem-and pyrethrum-based botanical insecticides (Pyerin75EC®, Nimbecidine® and Pyeneem 20EC®) and determine the influence of florally rich field margin vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Yang et al (2019) demonstrated that use of broad-spectrum synthetic insecticides prevented noncrop habitats from improving the population density of Harmonia axyridis Pallas (Coleoptera: Coccinellidae) in wheat fields. In general, pest control benefits more from the use of more selective insecticides that have low toxicity to natural enemies because larger natural enemy population are preserved (Fang et al 2018, Torres and Bueno 2018, Machado et al 2019, Ochieng et al 2022). Our studies show that matrine is a natural enemy friendly insecticide that is effective against A. gossypii and safe to H. variegata even when used at higher concentrations than it recommended by product labels.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2019) demonstrated that use of broad-spectrum synthetic insecticides prevented noncrop habitats from improving the population density of Harmonia axyridis Pallas (Coleoptera: Coccinellidae) in wheat fields. In general, pest control benefits more from the use of more selective insecticides that have low toxicity to natural enemies because larger natural enemy population are preserved (Fang et al 2018, Torres and Bueno 2018, Machado et al 2019, Ochieng et al 2022). Our studies show that matrine is a natural enemy friendly insecticide that is effective against A. gossypii and safe to H. variegata even when used at higher concentrations than it recommended by product labels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for example, in the USA, the resistance of the A. gossypii to organophosphates and pyrethroid was recorded as early as 1992 [ 172 ]. Despite the growing resistance, large farmers are forced to continue using chemical means of protection, combining them with biological methods [ 173 ] and botanical insecticides [ 174 , 175 , 176 ].…”
Section: Superfamily Aphidoideamentioning
confidence: 99%
“…The treatments were laid out using a 2 × 2 factorial arrangement in a randomized complete block design (RCBD) with four replications, giving a total of 16 plots. The experimental plots measuring 10 × 10 m were isolated from each other by a distance of 20 m. Lablab is a short crop; the 20 m separation was adopted as the compromise distance in conformity with typical smallholder land holdings (field sizes) as reported by Ochieng et al (2022) that also minimizes insect movement between any two experimental plots. Lablab monocrop was planted at a spacing of 0.5 × 0.3 m. In the maize-lablab intercrop, maize was planted at a spacing of 0.75 × 0.3 m, 1 seed per hill and lablab was planted between the maize rows at an intra-row spacing of 0.3 m, 2 seeds per hill.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Agricultural systems that rely heavily on mechanization and synthetic inputs such as pesticides disrupt non‐crop habitats where such natural enemies of pests seek refuge (Balzan et al, 2016; Bommarco et al, 2013) This calls for approaches that will balance the benefit of agricultural intensification and restore biocontrol service through enhancing the role of natural enemies in pest management. Conservation of important biological control agents provide a sustainable pest management option that can reduce dependency on the application of synthetic pesticides (Ochieng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%